(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
In the article the names of Ukrainian families bryophytes (Bryobionta – Holovmokhobionty) are given, most of which are for the first time and on that basis it was made a complete list of all parts of Ukraine bryoflora: Anthocerotophyta (Ukrainian name Kvitkorohofity), Marchantiophyta (Ukrainian name Marshantiofity), Bryophyta (Ukrainian name Holovmokhofity ). Proposed a number of new species epithets liverworts and mosses. In the formation of new titles of mosses the following was used: special, distinctive, characteristic features of gametophyte and sporophytes morphology, physiology, life forms, etc. (Viychatka korotkopovstysta – Trichocolea tomentella, Kuschomoh lysokhvostyi – Thamnobryum alopecurum, etc.); features specific habitats (Vapnychka creidyana – Cololejeunea calcarea; Vodnik protyposzeszhyi – Fontinalis antipyretica, Voloholyub richkovyi – Hygroamblystegium fluviatile, Vsiudnyk purpurovyi – Ceratodon purpureus etc.); importance of the taxon (typical race, decorative, etc.), for example, Holovmoh sriblyastyi – Bryum argenteum, Krasunchyk naiprecrasnishyi – Ptilidium pulcherrimum; latin counterparts, transliteration, the author is given proper the first description taxa (Bezzhylka szyrna – Aneura pinguis etc.); latin names are derived from proper names (Merkiya Blytha – Moerckia blyttii, Lazarenkiya Kozlova – Lazarenkia kozlovii); reasonable borrowing from other national names of genera and species – in Polish, Czech and other languages (for example, Zolotomoh (zlotnik – Polish.) – Campyliadelphus, Sobacozub (psizubec in Cech. – Cynodontium) and others.